Characteristics of the acquisition of sonorant consonants orthography in Brazilian children from a São Paulo municipality - Vaz, Suellen [UNESP]; Pezarini, Isabela De Oliveira [UNESP]; Paschoal, Larissa [UNESP]; Chacon, Lourenço [UNESP] (Sociedade Brasileira de Fonoaudiologia, 2015)
PURPOSE: To describe the spelling performance of children with regard to the record of sonorant consonants in Brazilian Portuguese language, to verify if the errors in their records were influenced by the accent in the word, and to categorize the kinds of errors found. METHODS: For this current survey, 801 text productions were selected as a result of the development of 14 different thematic proposals, prepared by 76 children from the first grade of primary school, in 2001, coming from two schools of a city from São Paulo, Brazil. Of these productions, all words with sonorant consonants in a syllabic position of simple onset were selected. They were then organized as they appeared as pre-tonic, tonic, and post-tonic syllables, unstressed and tonic monosyllables. RESULTS: The following was observed: the number of hits was extremely higher than that of errors; higher occurrence of errors in non-accented syllables; higher occurrence of phonological substitutions followed by omissions and, at last, orthographic substitutions; and higher number of substitutions that involved graphemes referring to the sonorant class. CONCLUSION: Considering the distribution of orthographic data between hits and errors, as well as their relationship with phonetic-phonological aspects, may contribute to the comprehension of school difficulties, which are usually found in the first years of literacy instruction.

Objetivos: Descrever o desempenho ortográfico de crianças, no que se refere ao registro de consoantes soantes do Português Brasileiro; verificar se os erros em seus registros sofrem influência do acento no interior da palavra e categorizar os tipos de erros encontrados. MÉTODOS: Para a presente pesquisa, foram selecionadas 801 produções textuais resultantes do desenvolvimento de 14 diferentes propostas temáticas, realizadas por 76 crianças da primeira série do ensino fundamental, em 2001, de duas escolas de um município paulista. Dessas, foram selecionadas as palavras com ocorrência de consoantes soantes em posição silábica de ataque simples. Foram, então, organizadas conforme aparecessem em sílabas pré-tônicas, tônicas, pós-tônicas, monossílabos átonos e tônicos. RESULTADOS: Observou-se: quantidade de acertos extremamente maior do que de erros; maior ocorrência de erros em sílabas não acentuadas; maior ocorrência de substituições fonológicas seguida de omissões e, por fim, de substituições ortográficas; e maior número de ocorrência de substituições que envolveram grafemas referentes à classe das consoantes soantes. CONCLUSÃO: Considerar a distribuição de dados ortográficos entre acertos e erros, bem como suas relações com aspectos fonético-fonológicos, pode contribuir para o entendimento das dificuldades escolares encontradas nas séries iniciais de alfabetização.
Características da aquisição da ortografia de consoantes soantes em crianças de um município paulista
Keywords: Handwriting; Language development; Child; Phonetics; Linguistics; Escrita manual; Desenvolvimento da linguagem; Criança; Fonética; Linguística